2023
DOI: 10.14814/phy2.15640
|View full text |Cite
|
Sign up to set email alerts
|

The impact of chronic stress on intracellular redox balance: A systems level analysis

Abstract: Chronic psychosocial stress is implicated in the onset and progression of noncommunicable diseases, and mechanisms underlying this relationship include alterations to the intracellular redox state. However, such changes are often investigated in isolation, with few studies adopting a system level approach. Here, male Wistar rats were exposed to 9.5 weeks of chronic unpredictable mild stress and redox status assays were subsequently performed on cardiac, hepatic, and brain tissues versus matched controls. The s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 79 publications
0
1
0
Order By: Relevance
“…Long-term exposure to psychosocial stress can induce enormous reactive oxygen species (ROS) and oxidative damage, triggering various cellular responses such as neurodegeneration, tissue damage, and cell death that are responsible for the depressive symptoms [12,44]. A study reported that chronic psychosocial stress causes redox perturbations in the brain tissue of rats [45]. In the present study, MDA and SOD were used as oxidative stress markers.…”
Section: Discussionmentioning
confidence: 99%
“…Long-term exposure to psychosocial stress can induce enormous reactive oxygen species (ROS) and oxidative damage, triggering various cellular responses such as neurodegeneration, tissue damage, and cell death that are responsible for the depressive symptoms [12,44]. A study reported that chronic psychosocial stress causes redox perturbations in the brain tissue of rats [45]. In the present study, MDA and SOD were used as oxidative stress markers.…”
Section: Discussionmentioning
confidence: 99%